2006
DOI: 10.2337/diacare.29.03.06.dc05-0695
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy in Type 2 Diabetes

Abstract: OBJECTIVE -To evaluate the efficacy and safety of add-on insulin glargine versus rosiglitazone in insulin-naïve patients with type 2 diabetes inadequately controlled on dual oral therapy with sulfonylurea plus metformin. randomized, parallel trial, 217 patients (HbA 1c [A1C] 7.5-11%, BMI Ͼ25 kg/m 2 ) on Ն50% of maximal-dose sulfonylurea and metformin received add-on insulin glargine 10 units/day or rosiglitazone 4 mg/day. Insulin glargine was forced-titrated to target fasting plasma glucose (FPG) Յ5.5-6.7 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(145 citation statements)
references
References 21 publications
(24 reference statements)
3
141
0
1
Order By: Relevance
“…The clinical trials showed that the use of basal insulin as an add‐on to OAD in patients with type 2 diabetes achieved 7% HbA1c, and approximately half of the patients experienced symptomatic hypoglycemia20, 21, 22, 23, 24. However, in real‐world practice, a retrospective USA study and two prospective studies in Ireland and Japan found that approximately just 20% of the patients taking basal insulin could achieve HbA1c <7% with a low rate of hypoglycemia16, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical trials showed that the use of basal insulin as an add‐on to OAD in patients with type 2 diabetes achieved 7% HbA1c, and approximately half of the patients experienced symptomatic hypoglycemia20, 21, 22, 23, 24. However, in real‐world practice, a retrospective USA study and two prospective studies in Ireland and Japan found that approximately just 20% of the patients taking basal insulin could achieve HbA1c <7% with a low rate of hypoglycemia16, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since diabetes is associated with progressive b-cell loss, many patients, especially those with long-standing disease, will eventually need to be transitioned to insulin, which should be favored in circumstances where the degree of hyperglycemia (e.g., ≥ 8.5%) makes it unlikely that another drug will be of sufficient benefit. 87 If triple combination therapy exclusive of insulin is tried, the patient should be monitored closely, with the approach promptly reconsidered if it proves to be unsuccessful. Many months of uncontrolled hyperglycemia should specifically be avoided.…”
Section: Position Statementmentioning
confidence: 99%
“…Similarly, though DIGAMI-2 trial[20] had three arms, it was chosen the insulin and non-insulin arms were clearly defined and outcomes compared between these two. Finally, 18 clinical trials [15,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were selected for meta-analysis (Figure 1). …”
Section: Literature Search Resultsmentioning
confidence: 99%